MiR-4787-5p Regulates Vascular Smooth Muscle Cell Apoptosis by Targeting PKD1 and Inhibiting the PI3K/Akt/FKHR Pathway. Issue 2 (August 2021) - Wang, Lei; Wang, Zhengbin; Zhang, Rui; Huang, Li; Zhao, Zhikang; Yang, Yuxia; Cui, Likun; Zhang, Shijie
Abstract : Abstract: Vascular smooth muscle cell (VSMC) dysfunction is the main cause of aortic dissection (AD). In this study, we focused on the role and mechanism of miR-4787-5p in regulating VSMC apoptosis. Real-time fluorescence quantitative polymerase chain reaction was used to detect the expression of miR-4787-5p in aorta tissues of AD (n = 10) and normal aortic tissues of donors (n = 10). Cell apoptosis was tested by TUNEL assay and Annexin V FITC/PI staining flow cytometry. The expression of PC1 and the PI3K/Akt/FKHR signaling pathway associated proteins in VSMCs was measured by Western blot. We found that the miR-4787-5p was highly expressed in aorta tissues of AD compared with 10 healthy volunteers. Meanwhile, PI3K/Akt/FKHR signaling pathway was inactive in the aortic tissue of AD. The overexpression of miR-4787-5p significantly induced VSMC apoptosis, and miR-4787-5p knockdown showed the opposite results. In addition, polycystic kidney disease 1 gene, which encodes polycystin-1 (PC1), was found to be a direct target of miR-4787-5p in the VSMCs and this was validated using a luciferase reporter assay. Overexpression of PC1 by a lentivirus packaging PC1-overexpression plasmid (LV-PC1) plasmids markedly eliminated the promotion of miR-4787-5p overexpression on VSMC apoptosis. Finally, it was found that miR-4787-5p deactivated the PI3K/Akt/FKHR pathway, as demonstrated by the down-regulation of phosphorylated (p-)PI3K, p-Akt, and p-FKHR. In conclusion, these findings confirm an important role for the miR-4787-5p/polycystic kidney disease 1 axis in AD pathobiology.